Lessons learned during Covid-19 concerning cheating in e-examinations by university students - Krambia-Kapardis, Maria (My University, 2021)
The Covid -19 pandemic and lockdown in many countries has left no option for many universities around the globe but to offer their examinations electronically. This has provided the opportunity for many students to try to defraud the system and cheat. The authors utilize two criminological theories to explain why students cheat and suggest policy implications. Purpose: The researchers investigate how students can be deterred from cheating, whether legal or ethical policies and procedures are effective and whether there are gender differences. Design/methodology: Utilising data on students undertaking midterm and final eexaminations as well as a control group of students who were caught cheating in an online mid-semester examination, the authors attempt to answer the research questions. Findings: No differences were found in cheating in terms of students’ gender or whether they were repeating a course or not. However, the study revealed that if there are more internal controls imposed and before the examination students are made to reinforce their academic integrity e-examination cheating is reduced. Originality: No other published study was carried out with students who were involved in cheating.
Keywords: e-examination cheating; Covid-19